Preliminary Study of the Effect of Technology Integration on the Growth of the Printing Industry in Indonesia - Haryasena Gusti Andayu; Handika Dany Rahmayanti (Jurnal Ilmiah Publipreneur, 2021)
Digital globalization in the economic sector is no exception in the printing industry. For hundreds of years the print media dominated for the dissemination of information. However, currently the dominance of the print media industry is now in danger of being shifted along with technological developments. This study shows how the growth of the print industry in Indonesia for several years. Based on the results of the study, the number of printing industries from 2011-2015 experienced a decline in almost all regions of Indonesia, including the provinces of West Java, East Java, DKI Jakarta, Banten, Kalimantan, Central Java and Sumatra. The decline in numbers occurred in the printing industry of newspapers, magazines, books and advertising. Especially for the packaging industry, it did not experience a significant decline and was relatively stable.